2017
DOI: 10.1093/pm/pnx097
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Upper Gastrointestinal Bleeding in Patients Taking Selective COX-2 Inhibitors: A Nationwide Population-Based Cohort Study

Abstract: Among coxibs users, H. pylori infection and history of PUB were especially important risk factors for UGIB. Further studies are needed to determine whether proton pump inhibitors might play a protective role in these at-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Lin et al [ 14 ] reported that cyclooxygenase-2 selective inhibitors (coxibs) significantly increased the incidence of UGIB, and various risk factors, including age, male gender, history of uncomplicated peptic ulcer disease, peptic ulcer bleeding, and H. pylori infection, contributed to the development of UGIB in coxibs users. The use of non-steroidal anti-inflammatory agents (NSAIDs) and anticoagulation agents associated with aging was considered to increase the development of UGIB by peptic ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al [ 14 ] reported that cyclooxygenase-2 selective inhibitors (coxibs) significantly increased the incidence of UGIB, and various risk factors, including age, male gender, history of uncomplicated peptic ulcer disease, peptic ulcer bleeding, and H. pylori infection, contributed to the development of UGIB in coxibs users. The use of non-steroidal anti-inflammatory agents (NSAIDs) and anticoagulation agents associated with aging was considered to increase the development of UGIB by peptic ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…Independent risk factors for bleeding among coxib users were age, male gender, diabetes, chronic renal disease, cirrhosis, history of PUD, H. pylori infection, and concomitant use of NSAIDs, aspirin, or thienopyridines. H. pylori infection and history of PU bleeding were important risk factors for rebleeding …”
Section: Helicobacter Pylori and Peptic Ulcer Diseasementioning
confidence: 99%
“…pylori infection and history of PU bleeding were important risk factors for rebleeding. 10 In a case-control study, Swiss investigators assessed the role of glucocorticoid consumption in the development of bleeding PUD.…”
mentioning
confidence: 99%
“…29 Furthermore, in a nationwide cohort study, it was demonstrated that patients taking COX-2 selective inhibitors have an increased risk of upper GI bleeding especially if they had history of uncomplicated peptic ulcer or Helicobacter pylori infection. 30 Our analysis found that patients receiving the combination of warfarin and selective COX-2 inhibitors experience an almost twofold increase risk in GI bleeding, similar to traditional NSAIDs. For those studies evaluating bleeding from any source, no significant increase was observed.…”
Section: Discussionmentioning
confidence: 68%